Tingkat Kepercayaan Diri melalui Pelatihan Komunikasi Interpersonal Metode Role Play - Eni Kusyati; Tut Wuri Prihatin; Rosviaziani Rosviaziani (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Self-esteem is an attitude or feeling of confidence in its own ability so that the individual concerned is not too anxious in any action. Objective: Know the difference in the confidence level before and after the provision of interpersonal communication training in Role play method in youth Orphanage Ar – Rodiyah. Research methods: : This type of research using quantitative studies with the design of the quasi experiment. The population in this study was all adolescent orphanages Ar-Rodiyah Semarang. The sampling technique used is perposive sampling with a total of 10 respondents. Data collection using confidence questionnaires . Data processed with paired samples test . Results of the study: That the average self-confidence score in the respondent before interpersonal communication training in the role play method is 109.3, the lowest score is 104 and the highest is 110. An average of the respondents ' confidence after interpersonal communication training is 114.8. The lowest lowest score is 109.00 and the highest is 117.00. There is a difference in the level of youth confidence before and after in providing interpersonal communication training in role play method, with a P value of 0.000 < α (0.05). Conclusion: There is a difference in the level of youth confidence before and after the provision of interpersonal communication training.